The Arni studies: Changes in the private sector of a market town, 1973-1983 - Harriss, Barbara (International Food Policy Research Institute, 1991)
In a predominantly agrarian region, development of the nonfarm economy is materially affected by the development of the agricultural sector. Agriculture supplies food, raw materials, and surplus labor for agro-industry. Agriculture also supplies the financial resources necessary to the organization of nonfarm firms. These resources can be mobilized through the terms of trade, through the savings and investments of both farmers and agricultural traders, and through direct and indirect taxation. Furthermore, demand from the agricultural sector stimulates nonfarm activity. Nonfarm economic activity not only is decentralized in villages (see Chapter 10) but is concentrated in market towns, in which northern Tamil Nadu is comparatively rich.